Feto maternal outcome in placenta previa and morbidly adherent placenta - Khan, Somy; Rawat, Rajendra Prasad; Meena, Santosh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Placenta forms the most important link between the developing foetus and the mother. The placenta’s health is crucial for the foetus’ proper growth and development. The outcome of pregnancy is changed when there is a change in the placental location or architecture for both the mother and the foetus. No matter the cause, placenta previa increases maternal and foetal risks by several times. Aim and objectives of current study are to investigate the incidence of placenta previa in hospital obstetric patients and the maternal and fetal outcome in cases of placenta previa. Methods: 100 patients delivered in the Govt. Medical College, Kota with cases of placenta previa. Risk factors like Gestational age at the onset of bleeding, expectant management, gestational age at delivery and the mode of delivery. The birth weight and APGAR score of the newborn were observed. Results: The risk of placenta previa is 3 time higher in multigravida than primigravida. 52% chances of placenta previa with male babies. Peak incidence of bleeding is noted around 34-36 weeks. 92% of placenta previa cases were delivered LSCS. PPH was main morbidity out of all morbidities. 55% of babies were less than 2.4 Kg. 44% were anterior, 38% posterior and rest 6% central placenta previa. Conclusions: Placenta previa poses a serious risk to both the mother and the foetus, whether it is accidentally discovered by ultrasound or as a result of a clinical emergency like a haemorrhage in the mother. The best outcome can be achieved with an accurate diagnosis, prudent expectant management, blood transfusion as necessary, and prompt delivery.